Brazilian banana, guava, and orange fruit and waste production as a potential biorefinery feedstock - Pereira, Beatriz Salustiano [UNESP]; Freitas, Caroline de [UNESP]; Vieira, Rogerio Martins [UNESP]; Brienzo, Michel [UNESP] (Springer Nature, 2022)
Fruit production worldwide is over 675 million tons per year. Brazil is responsible for the production of 43.6 million tons of fruits per year, which makes the country stand out in the generation of fruit and food residues. About 35% of all agricultural production in Brazil is wasted and, from that, 42% is destined for inappropriate places such as public roads and rivers, causing environmental, sanitary, and social impacts. From the total agricultural production, 16.8 million tons are orange, 7.1 million tons are banana, and 0.6 million tons are guava, which makes these fruits of great importance to the country and consequently generate a huge amount of residues. Besides that, the restaurants/food industries also discard a large volume of waste. The review shows the importance of these residues and a scenario of utilization in order to reduce environmental impacts and add value to them. Bioenergy and value-added products are from industrial interest and can collaborate in economic, social, and environmental aspects.
Keywords: Biomass; Environmental alternatives; Food waste; Fruits; Sustainability